1976
DOI: 10.1152/ajplegacy.1976.230.5.1455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein intake on weight gain and plasma amino acid levels in uremic rats

Abstract: Chronically uremic rats weighing approximately 180-200 g and sham-operated controls of similar weight were pair fed diets containing 5, 15 or 23% protein for 10-12 wk. At each level of protein intake, uremic animals gained less weight and had lower protein efficiency ratios than controls. In addition, certain plasma amino acid levels were altered in the uremic animals. These included tyrosine and the tyrosine/phenylalanine ratio, which were decreased, and citrulline, glycine, and the methylhistidines, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
2

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 0 publications
3
10
2
Order By: Relevance
“…Adult stature is usually far below that expected for a child's genetic potential, even with adequate dialysis, treatment of acidosis, administration of phosphate binders, nutritional counseling, and supplemental vitamin D ( 1 , 2). Similar findings have been noted in other animal models of chronic renal insufficiency (3)(4)(5). Disturbances in the growth hormone/somatomedin system have been implicated in the etiology of the reduced growth rates of children with renal insuffi-ciency (6,7 ) ; however, the mechanisms remain unclear.…”
supporting
confidence: 77%
“…Adult stature is usually far below that expected for a child's genetic potential, even with adequate dialysis, treatment of acidosis, administration of phosphate binders, nutritional counseling, and supplemental vitamin D ( 1 , 2). Similar findings have been noted in other animal models of chronic renal insufficiency (3)(4)(5). Disturbances in the growth hormone/somatomedin system have been implicated in the etiology of the reduced growth rates of children with renal insuffi-ciency (6,7 ) ; however, the mechanisms remain unclear.…”
supporting
confidence: 77%
“…Increased creatinine is a commonly used marker of decreased renal function. Decreased body weight in patients with end-stage renal disease can be explained by malnutrition and increased catabolism attributable to uremia or chronic hemodialysis (42)(43)(44). We showed that serum cLDL was significantly higher in uremic patients than in controls.…”
Section: Discussionmentioning
confidence: 74%
“…At each level of dietary protein, net protein degradation was higher in CRF rats; the difference was greatest when 10% protein was fed even though the degree of azotemia was least in this group of rats. It is possible that the adverse effect of the 10% protein diet was the result of an inadequate protein intake, since at most 10 g of food was allowed each day and the average weight of both CRF and control rats decreased (2,9). When CRF rats were given more protein, which lead to more severe azotemia, it is possible that these rats were acidotic, and that this contributed to the significant increase in net protein degradation compared with that in muscles of control rats.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated bicarbonate was used to estimate each rat's acid-base status to eliminate the influence of varying degrees of Co2 retention during anesthesia and preparation for perfusion. The perfusate consisted of Krebs-Henseleit bicarbonate buffer, 3.5 g/dl bovine serum albumin (fraction V; Miles Laboratories, Elkhart, IN) that had been dialyzed for 48 h at 4VC against Krebs-Henseleit bicarbonate buffer, aged, washed human erythrocytes (hematocrit 25%), 10 mM glucose, and amino acids in concentrations found in rat plasma (9). In some experiments in studies 1 and 3, 1 mU/ml of regular pork insulin (Eli Lilly & Co., Indianapolis, IN) was added and the glucose concentration in the perfusate was increased to 20 mM because preliminary studies showed that glucose fell to very low levels if the initial glucose concentration was 10 mM.…”
Section: Methodsmentioning
confidence: 99%